2010
DOI: 10.1093/pubmed/fdq087
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and home environment predictors of screen viewing among Spanish school children

Abstract: Environmental and sociocultural factors influence the time children spend in screen viewing. Parents play a central role in child's screen viewing; therefore, interventions that target environmental and family TV viewing practices are likely to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 40 publications
(24 reference statements)
6
51
2
Order By: Relevance
“…A total of 18 studies investigated the influence that a child's body mass index (BMI) has on measures of sedentary behaviour; half of these found null associations 13 19 48 54 63 64 66 67. In contrast, two studies that used accelerometry to measure sedentary behaviour found that having a higher BMI was associated with more time spent in sedentary behaviour 13 19.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 18 studies investigated the influence that a child's body mass index (BMI) has on measures of sedentary behaviour; half of these found null associations 13 19 48 54 63 64 66 67. In contrast, two studies that used accelerometry to measure sedentary behaviour found that having a higher BMI was associated with more time spent in sedentary behaviour 13 19.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies that assessed the relationship between pubertal stage and measures of sedentary behaviour were identified48 60 63 (table 2). One study found that more mature children spent more time in screen-based sedentary behaviour49; a second found that more mature children spent more time in non-screen-based sedentary behaviour 68.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the research on restrictive mediation tends to be rather inconsistent, depending on the type of medium, content, or outcome analyzed. For example, restrictive mediation has been utilized by parents to decrease overall media use (i.e., Barradas, Fulton, Blanck, & Huhman, 2007;Carlson et al, 2010;Cillero & Jago, 2011;Livingstone & Helsper, 2008;Nathanson, 2002;Ramirez et al, 2011;te Velde et al, 2011), but the use of content restrictions appears to increase the amount of time spent viewing TV in at least one study (Vandewater, Park, Huang, & Wartella, 2005). Additionally, rules regarding TV content decrease the amount of violent and pornographic content (Livingstone & Helsper, 2008;Woolf, 2009) and child entertainment (i.e., cartoons;Truglio, Murphy, Oppenheimer, Huston, & Wright, 1996), and increase educational and prosocial content viewed by children (Woolf, 2009).…”
Section: Restrictive Mediationmentioning
confidence: 99%
“…Studies have shown that parents play a central role in their children's screen viewing and that the time that children spend in screen viewing is influenced by both environmental (e.g. media availability in bedrooms) and socio-cultural factors (57)(58)(59) .…”
Section: Television Viewingmentioning
confidence: 99%